The Internet and the Law - Dugan, Bob; Dugan, Benedict (Victoria University of Wellington Law Review, 2002)
The Internet and related technologies are impacting on the law like no other phenomenon in our lifetime. The impact is felt from the basic institutions of contract and tort to the remote corners of competition law and securities law. The legislative system is not coping with the challenge, as demonstrated by the paralysis over the Electronic Transactions Bill and the Crimes Amendment Bill (No 6). This article opens with some background material about the Internet, proceeds to consider its impact on eight areas of the law and concludes with some observations about the feasibility and direction of regulation.